OUTCOME ANALYSIS OF POSTOPERATIVE DECOMPRESSION AND STABILIZATION PATIENTS WITH DEGENERATIVE THORACO-LUMBAR VERTEBRAL FRACTURE - Henky, Jefri (Jurnal EduHealth, 2022)
Degenerative thoraco-lumbar fractures are structural and functional changes that occur in the thoracal and lumbar vertebrae regions. The degenerative process that occurs as a result of the aging process in each individual is different, as well as in the spinal region. The type of data used in this study is secondary data obtained through medical records conducted by researchers at the Semen Padang Hospital Medical Record Unit, the data includes variables of age, gender, occupation, smoking status, BMI, level of thoraco-lumbar fracture, mean VAS postoperative decompression and stabilization at Semen Padang Hospital. The research was conducted in December 2021 until completion which includes the preparation and reporting stages. This research is a form of analytical study with a cross sectional design. The affordable population was postoperative decompression and stabilization surgery patients in 2019 as many as 30 patients with a total sampling technique. Univariate data analysis is presented in the form of frequency distribution and percentage and data processing using computerized SPSS version 24.0 program. And the results of this study explain that based on the characteristics of the patient's risk factors, the most age is the early elderly 46-55 years, namely 10 people (33.3%), the most gender is female, namely 16 people (53.3%), occupation, which most people are not lifting weights, namely 22 people (73.3%), smoking status is not smoking, namely 24 people (80.0%) and the highest BMI is normal (≥18.5 - <24.9) which is 19 people (63.3%). The highest number of damage levels were 1 and 2 damage levels, respectively, which were 14 people (46.7%). The most pain based on VAS was mild pain, namely 12 people (40.0%). There was a significant effect of the number of levels of damage on the pain scale in postoperative decompression and stabilization patients at Semen Padang Hospital (p= 0.021), and there was a significant effect of the number of levels of damage on the level of post operative decompression and stabilization pain in degenerative thoraco-lumbar fracture patients in Semen Padang Hospital